Menyibak Dimensi Ekologis dan Dimensi Humanis Upacara Roko Molas Poco dan Ensiklik Laudato Si’ Artikel 89-92 - Hyronimus Dominggus; Pius Pandor (Fakultas Ilmu Budaya, Universitas Jambi, 2022)
The focus of this study is to find the similarities and actuality of the ecological and humanist dimensions in the Roko Molas Poco ceremony with Pope Francis' Encyclical Laudato Si’ on a universal communion. In the Roko Molas Poco ceremony, the relational aspect between humans and their fellow humans is emphasized as well as between humans and nature. This ceremony describes the way the Manggarai people treat nature and humans. This basic assumption seems to be in line with the idea of ​​Pope Francis in Laudato Si'. Humans depend on nature, and nature also depends on humans who manage it. Thus, from the human side, the way to relate to nature is not to exploit it on a large scale, but to cultivate it while still paying attention to its conservation. Likewise, the sense of humanity is truly the basic foundation in relating to others. This study uses qualitative research with a comparative approach between the Roko Molas Poco ceremony and the idea of ​​a Universal Communion in the Encyclical Laudato Si'. This study resulted in the finding that in the Roko Molas Poco ceremony, aspects of the ecological and human dimensions have similarities in the concept of a Universal Communion contained in Laudato Si’.